Critical state of fly ash-bottom ash mixture - A. Rahman, Marwa (2010)
The burning of coal in the process of generating electricity, leads to the production of solid waste such as the fly ash and bottom ash. Numerous studies had been carried out to determine the mechanical properties of fly ash and also bottom ash. An extension of these studies is necessary in order to explore further usage of these ashes, in particular when mixed together in optimum percentage. The critical state boundary surface of the soil or material is important to identify the limit of stress imposed from various stress level and stress history. Hence, this study aimed at developing the critical state boundary surface of a mixture of 60% fly ash and 40% bottom ash by weight, is vital. The results obtained could be used as a guideline when working in the future with coal ash mixture of the same mix ratio. The samples used in this study were collected from Tanjung Bin power station in Johor, Malaysia. The fly ash-bottom ash mixture used in this study had a liquid limit of about 22% and behaved as non-plastic material. The mixture is classified as well-graded sandy silt with specific gravity of about 2.36. From the compaction test it showed that the maximum dry unit weight of this mixture is 14.54 kN/m3, achieved at 8.5% optimum water content. The critical state parameters of the mixture obtained in this study are ?= 0.032, ? = 0.013, ?=0.035, N=1.85 and M=1.152. From the critical state parameters obtained, the critical state boundary surface of fly ash- bottom ash mixture (60:40% by weight) had been established